Electronic Poster Abstracts 2020
DOI: 10.1136/neurintsurg-2020-snis.67
|View full text |Cite
|
Sign up to set email alerts
|

E-031 Dural arteriovenous fistulas without cortical venous drainage: presentation, treatment and outcomes

Abstract: of Science databases. With the assistance of a librarian, we used various combinations of keywords such as Moyamoya disease, ischemic stroke, hemorrhagic stroke, antiplatelet, and the names of individual antiplatelet agents. Titles and abstracts were screened by the first two authors (MAS and MEE), with a full-text review of relevant papers. Articles were included if they examined the effect of antiplatelet therapy on ischemic or hemorrhagic stroke or survival in patients with moyamoya disease. Results Out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 0 publications
1
14
2
Order By: Relevance
“…14 Likewise, in the recent Consortium for Dural Arteriovenous Fistula Outcomes Research (CONDOR) database with a mean follow up of 38 months, analysis of Borden Type I dAVF, 0% of the 103 conservatively managed lesions progressed to a higher grade; however, 5/218 (2.3%) of the treated dAVFs upconverted to a Borden type II or III. 6 Another rationale for treatment of low-grade fistulae is possible palliative symptomatic relief. Samaniego et al of CONDOR suggested treatment may yield superior symptomatic control when angiographic obliteration is achieved 6 ; though, propensity-matched analysis of the same cohort revealed no difference in clinical outcomes between observed and treated patients when accounting for incomplete treatments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14 Likewise, in the recent Consortium for Dural Arteriovenous Fistula Outcomes Research (CONDOR) database with a mean follow up of 38 months, analysis of Borden Type I dAVF, 0% of the 103 conservatively managed lesions progressed to a higher grade; however, 5/218 (2.3%) of the treated dAVFs upconverted to a Borden type II or III. 6 Another rationale for treatment of low-grade fistulae is possible palliative symptomatic relief. Samaniego et al of CONDOR suggested treatment may yield superior symptomatic control when angiographic obliteration is achieved 6 ; though, propensity-matched analysis of the same cohort revealed no difference in clinical outcomes between observed and treated patients when accounting for incomplete treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Our institutional experience combined with 3 comparative studies from the systematic literature review yielded 495 total patients who possessed a Borden Type I intracranial dAVF. 4,6,7 From these, 469 patients had primary outcome measures that were sufficiently detailed for inclusion in the final pooled quantitative synthesis, which included 279 patients who underwent intervention, and 190 who were observed (Table 1). The most common reported presenting symptoms was pulsatile tinnitus in 65% of patients, followed by orbital or ocular symptoms in 32% of patients, and headache in 27% of cases (Table 2).…”
Section: Meta-analysis and Pooled Quantitative Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…However, these cases can require hours of radiation exposure for the patient over potentially multiple embolization sessions, and there is a modest risk of DAVF recurrence even after initial angiographic cure. Based on analyses of the CONDOR database, obliteration of a low-grade DAVF after a single embolization session was achieved in <40% of cases, 10 and the rate of recurrent arteriovenous shunting after angiographic cure (which required a mean of >2 embolization sessions) was 7%. 11 Based on these findings, SRS may warrant consideration as a first-line treatment for unruptured DAVFs.…”
mentioning
confidence: 99%